Deposition of B4C Microparticles on Boiling Surface in Boric Acid Solution - Han, Sol-Chan; James Daub, Kevin; Jung, Sang-Hyuk; Ju Kim, Min; Yeon, Jei-Won; Song, Kyuseok (Asian Journal of Chemistry, 2013)
The deposition of B4C microparticles was carried out under boiling water conditions. We investigated the effect of heater power, the presence of Fe or Ca ions and the presence of pre-formed oxide layers on the deposition of B4C microparticles. Starting from a power level inducing bulk boiling, the deposition amount of B4C microparticles increased with an increase of heater power. However, a maximum deposition condition was observed between bulk boiling and film boiling states. The amount of deposited B4C microparticles decreased in the presence of metal ions (Fe or Ca). The metal ions acted as flocculants to decrease the dispersive stability of B4C microparticles rather than a source material for a porous oxide layer to increase the deposition of B4C microparticles. It was observed that B4C microparticles deposited much easier on bare stainless steel surfaces than on surfaces covered with an iron oxide layer under boiling water conditions.